Magnetocaloric Effect in Lightly‐Doped Fe5Si3 Single Crystals - Guixin Cao; Satoshi Okamoto; Junjie Guo; E. D. Specht; Thomas Z. Ward; M. A. McGuire; John D. Budai; Matthew F. Chisholm; David Mandrus; Brian C. Sales; Zheng Gai (Advanced Physics Research, 2023)
Abstract Development of promising new materials for above room temperature magnetic cooling applications relies on careful balancing of structure and composition to maximize accessible metastable phases that can drive a strong magnetocaloric effect (MCE). However, the working temperatures of these materials may fall outside of desired application windows. In this work, it is shown that it is possible to control metastable phase stability temperatures of Fe5Si3 through selection of appropriate spin and charge doping. Here, the parent material's desired structure appears only within a narrow temperature range from 1098 to 1303 K. Doping with Mn and P is shown to allow stabilization of the parent's high temperature phase and resulting MCE to room temperature. The structural and magnetic properties, and the magnetocaloric effect of single crystal Fe4.83Mn0.16Si2.91P0.09 (FMSP) are investigated experimentally and theoretically. A first‐order magneto‐elastic transition is observed at 348 K, where magnetic onset is accompanied by a change in lattice volume without an apparent change in crystal symmetry. Although the trace Mn and P doping are found to decrease the TC, the maximum magnetic entropy change ΔSMax(T) and the relative cooling power (RCP) of FMSP are enhanced compared to polycrystalline Fe5Si3. As a result, an intrinsically broader entropy change over a larger temperature span is generated in the lightly doped single crystal of Fe5Si3. The magnetic moment of the system is also enhanced. Density functional theory (DFT) calculations are performed to gain microscopic insights into the experimental findings. The results suggest that the hexagonal Fe5Si3 is a new giant room temperature MCE material that is on par with La–Fe–Si and Fe‐Mn‐P‐Si systems.